Associations between social and behavioural factors and the risk of late stillbirth – findings from the Midland and North of England Stillbirth case‐control study. (28th October 2020) - Heazell, AEP; Budd, J; Smith, LK; Li, M; Cronin, R; Bradford, B; McCowan, LME; Mitchell, EA; Stacey, T; Roberts, D; Thompson, JMD
Abstract : Objective: To investigate behavioural and social characteristics of women who experienced a late stillbirth compared with women with ongoing live pregnancies at similar gestation. Design: Case‐control study. Setting: 41 maternity units in the UK. Population: Women who had a stillbirth ≥28 weeks' gestation ( n  = 287) and women with an ongoing pregnancy at the time of interview ( n  = 714). Methods: Data were collected using an interviewer‐administered questionnaire which included questions regarding women's behaviours (e.g. alcohol intake and household smoke exposure) and social characteristics (e.g. ethnicity, employment, housing). Stress was measured by the 10‐item Perceived Stress Scale. Main outcome measure: Late stillbirth. Results: Multivariable analysis adjusting for co‐existing social and behavioural factors showed women living in the most deprived quintile had an increased risk of stillbirth compared with the least deprived quintile (adjusted odds ratio [aOR] 3.16; 95% CI 1.47–6.77). There was an increased risk of late stillbirth associated with unemployment (aOR 2.32; 95% CI 1.00–5.38) and women who declined to answer the question about domestic abuse (aOR 4.12; 95% CI 2.49–6.81). A greater number of antenatal visits than recommended was associated with a reduction in stillbirth (aOR 0.26; 95% CI 0.16–0.42). Conclusions: This study demonstrates associations between late stillbirth and socio‐economic deprivation, perceived stress and domestic abuse, highlighting the need for strategies to prevent stillbirth to extend beyond maternity care. Enhanced antenatal care may be able to mitigate some of the increased risk of stillbirth. Tweetable Abstract: Deprivation, unemployment, social stress & declining to answer about domestic abuse increase risk of #stillbirth after 28 weeks' gestation. Tweetable Abstract: Deprivation, unemployment, social stress & declining to answer about domestic abuse increase risk of #stillbirth after 28 weeks' gestation. This article includes Author Insights, a video abstract available at https://vimeo.com/rcog/authorinsights16543